Role of myosin heavy chains in adaptive and pathological processes – a systematic review - Busłowicz, Tomasz; Kler, Anna; Grzesica, Aleksandra; Malerczyk, Martyna; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
Introduction: Myosin heavy chains (MHCs) are the core group of proteins that builds skeletal and cardiac muscle. Their characteristic is determined depending on MHC isoform, its percentage distribution and cross-sectional area of fibers it builds. These variables along with MHC gene expression undergo changes during adaptive and pathological processes. Purpose: The aim of the article was to review significant studies on MHCs; summarize current knowledge in terms of adaptation, aging and pathological processes; provide interpretation and reach conclusions. Methods: The literature review was conducted with topic-related articles found on platforms such as NCSI, PubMed, Google Scholar, using terms “MHC”, “MYH”, “Muscle adaptation”, “myosin heavy chains” and “skeletal muscle” in the searching process. Current Knowledge: During adaptation to physical activity, changes in MHCs are dependant on the type of activity. Endurance training decreases expression of MYH4 gene and increases expression of MYH7. It results in transformation of MHC II towards MHC I and in stimulation of mitochondrial biogenesis. Resistance training favors MHC IIa and hypertrophy. Aging process is associated with increased expression of MHC I but lifelong exercises help to preserve favorable fiber profile. MHC ratios and gene expressions are also altered in pathological conditions, such as obesity, neoplasms and heart disorders. MHCs play a significant role in fracture healing, and their serum levels may reflect soft tissue injuries. Conclusions: MHC isoform distribution is associated with muscle adaptation and dysfunction. Understanding its regulation offers new perspectives in disease prevention, rehabilitation, and therapeutic strategies for muscle and cardiovascular health.